2014
DOI: 10.17795/ijep21725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Virulence Factors Distribution in Uropathogenic E. coli Isolates From Phylogenetic Groups B2 and D

Abstract: Background: Urinary tract infections are a significant health problem, with Escherichia coli as a primary pathogen in approximately 80% of cases. The pathogenesis of E. coli in urinary tract infections is attributed to the production of virulence factors and phylogenetic background groups. Objectives: The aim of this study was to determine differences in prevalence of virulence factors of E. coli isolates from phylogenetic groups B2 and D, collected from patients with urinary tract infections. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
(24 reference statements)
1
12
1
Order By: Relevance
“…As reported previously, most of the uropathogenic E.coli isolates belonged to the phylogenetic group B2, D [25] and most of VGs were more prevalent in phylogenetic group B2 and/or D [26][27][28][29]. In the study, the number of VGs detected varied within the phylogroups and was significantly higher in group B2 than in other three groups.…”
Section: Virulent Genessupporting
confidence: 73%
“…As reported previously, most of the uropathogenic E.coli isolates belonged to the phylogenetic group B2, D [25] and most of VGs were more prevalent in phylogenetic group B2 and/or D [26][27][28][29]. In the study, the number of VGs detected varied within the phylogroups and was significantly higher in group B2 than in other three groups.…”
Section: Virulent Genessupporting
confidence: 73%
“…26 The virulence genes of UPEC bacteria such as iroN, iucD and irp2 have been previously recorded from Iran. 11,12 However, according to published data, there is no information on the occurrence of these genes in FeEC isolates. The distribution of the ompT gene among the studied isolates was also similar to that in the previously reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been done in different parts of Iran in order to investigate the frequency of virulence genes among UPEC. [11][12][13] However, there is no information about the frequency of virulence mediators in FeEC isolated from human in Iran. Therefore, this study was conducted to examine the distribution of 8 virulence factors, including type 1 fimbriae (fimH), iron-regulated gene homologue adhesion (iha), alpha-hemolysin (hlyA), outer membrane protease (ompT), aerobactin (iucD), yersiniabactin (irp2), salmochelin receptor (iroN) and cytotoxic necrotizing factor 1 (cnf1) in E. coli strains isolated from human feces in Zabol, southeast of Iran, by using the multiplex polymerase chain reaction (PCR) method.…”
mentioning
confidence: 99%
“…E. coli virulence genes are also main factors in the etiology of UTIs, as well as human susceptibility factors (1,22,23). It has been reported that the UPEC strains which cause most UTIs form a genetically different group with multiple virulence factors (24). Generally, the combination of various factors in host and pathogen has determined the individual susceptibility to UTIs.…”
Section: Discussionmentioning
confidence: 99%